Determination of heavy metals in fish and seafood - Saim, Hafizah (2011)
The aim of this study was to detennine concentrations level of heavy metals (zinc, copper, cadmium and lead) in edible parts of fish and seafood. The levels of these metals in fish (6) and seafood (4) purchased from the Kelantan markets were measured. The conventional wet acid digestion method was used for the mineralization of these samples prior to the quantitative detennination by graphite furnace atomic absorption spectrometry (AOAC International, 2002). The heavy metal concentrations in the fish ranged from (0.020 ± 0.01 to 0.900 ± 0.12 μg/g ww) for Cu, (2.593 ± 0.36 to 9.610 ± 0.08 μg/g ww) for Zn, (0.025 ± 0.0025 to 0.150 ± 0.0014 μg/g ww) for Cd and (0.004 ± 0.014 to 0.110 ± 0.026 μg/g ww) for Pb. Meanwhile, the heavy metal concentrations in seafood ranged from (0.440 ± 0.06 to 9.300 ± 0.10 μg/g ww) for Cu, (1.669 ± 0.46 to 9.800 ± 0.23 μg/g ww) for Zn, (0.340 ± 0.0032 to 0.930 ± 0.0023 μg/g ww) for Cd and (0.006 ± 0.017 to 0.180 ± 0.029 μg/g ww) for Pb. In average, all heavy metals in seafood were higher than in fish. This study also showed that the heavy metals concentration in demersal fish and seafood were higher compared to pelagic species. The metal concentrations in the pelagic species ranged from (0.020 ± 0.01 to 0.672 ± 0.24 μg/g ww) for Cu, (2.593 ± 0.36 to 5.693 ± 0.16 μg/g ww) for Zn, (0.025 ± 0.0025 to 0.041 ± 0.0023 μg/g ww) for Cd, and (0.004 ± 0.014 to 0.005 ± 0.022 μg/g ww) for Pb. Meanwhile, the metal concentrations in demersal species ranged from (0.440 ± 0.06 to 9.300 ± 0.10 μg/g ww) for Cu, (1.669 ± 0.46 to 9.800 ± 0.23 μg/g ww) for zinc, (0.130 ± 0.0023 to 0.930 1 ± 0.0023 μg/g ww) for Cd and (0.006 ± 0.017 to 0.180 ± 0.029 μg/g ww) for Pb. Comparison of heavy metals concentration between pelagic and demersal species were difficult due to the lack of literature information from other studies at more global scale. However, all the average values of these metals from all populations were lower than guidelines and regulations stipulating maximum permissible levels set by the Malaysian Food Act 1983 and Food Regulations 1985 Fourteen Schedule. These metals concentration found in fish and seafood were also considered to be lower compared with literature in other studies. Thus, these concentration levels should result in no acute toxicities of heavy metals since they are lower than the limit. It was concluded that heavy metals concentration level in commercial fish and seafood must be monitored comprehensively and periodically with respect to the consumer health.